Digital and Information Technologies in Economics and Management Proceedings of the International Scientific and Practical Conference "Digital and Information Technologies in Economics and Management" (DITEM2022) - Gibadullin, Arthur (Lecture Notes in Networks and Systems, 2023)
X, 170 p. 71 illus., 53 illus. in color.